PARTISIPASI POLITIK MASYARAKAT DESA DALAM PEMILIHAN PRESIDEN TAHUN 2019 DI KECAMATAN BANGUNTAPAN KABUPATEN BANTUL - Laxchyta Bara Abadi; Kushandajani - - (Journal of Politic and Government Studies, 2021)
Democracy is a form of a country's political system. Wilson Churchill said that the best successful system of government, but no system is better than that. Participation is very necessary in a country to advance the country itself, especially big countries in the world including Indonesia itself which has a heterogeneous society. Participation from the community can be a benchmark for the state to see what it wants. The general election is a forum for community members to elect their representatives because the people themselves will make that person their leader or president. But the reality is that Banguntapan District is still a sub-district with a low level of participation. The purpose of this paper is to identify the low participation factor, analyze the level of participation and find out the reasons for the low level of participation of rural communities in Banguntapan District in the 2019 Presidential Election. With the theory of public perception and the theory of motivation and indicators used, the reality that occurs in the field is that there are ideological factors that play a big role. The people of Banguntapan District have their perceptions regarding the 2019 Election, these perceptions are more negative. This means that they have the view that their vote does not influence government decisions. In general, the 2019 Election in Banguntapan District has been carried out well but there are still shortcomings, such as village people who are still politically indifferent or less aware of the election because they think that voices like them will not be heard. The suggestion that can be given to the Bantul KPU is to consider various solutions to overcome the low participation rate in Banguntapan District. The advice that can be given to the people of Banguntapan District is that they are expected to continue to participate in various democratic activities